Caught By Private Law: A Review Of Visitors’ Jurisdiction In Canada - Strombergsson-Denora, Adam (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
Visitors, an office in charitable corporations that occupies the position of the Superior Court in all matters pertaining to the charity, are a forgotten area of law in Canada. This article resurrects the jurisdiction by explaining its utility for university corporations. Visitors are private courts of appeal from university decisions. They are empowered to adjudicate academic as well as legal disputes relating to relationships between the university, its officers, its professors, and its students. The article lays out the private law origins of the office and contrasts this approach with the administrative law model more recently in vogue. The administrative law approach to visitation has, over the course of the twentieth century, eroded the jurisdiction, yet it appears from Canadian practice that the jurisdiction remains eminently useful across the country. The article details just how the visitor’s office has been used in Canadian universities beginning in 1803 going up to 1992. In so doing, the office’s strong points as well as its weaknesses are discussed.